SMART CP (Simulation Methods Analysis Rule Tech Chemistry Profession) Company and Android Application in Three Areas Regular Work for Future Solution to Decrease Unemployment and Develop Human Resources - Ahmad Saifullah; Ahmad Kamrullah Aras; Yuliana Yuliana (Pancaran Pendidikan, 2020)
Unemployment is one of the main employment challenges that challenge developing countries, including Indonesia. (Muslim,2014). There are many competent human resources but many are unemployed, this is because there are some fraudulent parties or their reach is very difficult. SMART CP is a Company and application designed specifically in the field of chemistry, it places one's work in one of the fields they will choose from 3 Chemistry jobs provided by SMART CP (Teachers, Analysts / Labs, and Entrepreneurs) This application has been created to decrease unemployment and develop Human Resources. The research methods used are qualitative and quantitative as well as additions to the research methods. some purpose of this Application first is, to develop students' online learning media, to facilitate teaching staff in the bookkeeping of teacher learning devices, to obtain information directly vertically from the Ministry of Education and Culture.